DETERMINASI KETEPATAN WAKTU PELAPORAN KEUANGAN PADA PERUSAHAAN SEKTOR PERBANKAN - Rika Kartika; Ratu Sifa Ni’mah (Yayasan Education and Social Center, 2026)
Financial statements must be presented in a timely manner to remain relevant; however, delays still occur. This study examines the effect of profitability and leverage on the timeliness of financial reporting in banking companies listed on the Indonesia Stock Exchange during 2020–2024. A quantitative approach with multiple linear regression is used on 11 companies (55 observations). The results show that partially, profitability (sig 0,564 > 0,05) and leverage ((sig 0,442 > 0,05) have no significant effect (H1 and H2 rejected). However, simultaneously, they have a significant effect (sig 0,042 < 0,05; H3 accepted). The R Square value of 0.205 indicates a 20.5% contribution. In conclusion, profitability and leverage do not affect timeliness individually but have a joint effect with low explanatory power, indicating the influence of other factors such as firm size, liquidity, audit quality, and corporate governance.